A phosphorus-free water dispersant and its preparation method
By using maleic acid-acrylic acid copolymer and other raw materials, the scaling problem caused by the accumulation of calcium and magnesium ions in the coal gasification circulation water system is solved, and high-efficiency scale inhibition and environmental protection long-term stability is achieved It operates, meets strict environmental protection requirements, and provides good antioxidant and chlorine resistance.
Patent Information
- Application Number
- CN202110719221.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-06-28
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-06-28
AI Technical Summary
Calcium and magnesium ions accumulation in coal-to-oil coal gasification circulating water system lead to frequent scaling of equipment pipelines. The existing phosphorus-containing scale inhibitors cannot meet the strict environmental protection requirements. It is necessary to develop apatoma-free water dispersant to ensure the long-term stability of the system. Operation and environmental protection.
The apat-free water dispersant is prepared by raw materials such as maleic acid-acrylic acid copolymer, polyepoxysuccinic acid, acrylic acid-acrylate-sulfonate copolymer, hydrolyzed polymaleic anhydride and sodium lignin sulfonate, and the copolymer is used. The complex and synergistic effect of the suspension selectively adsorbs the surface of suspended substances, prolongs the crystallization induction period, slows down the scale, and has antioxidant and chlorine resistance.
It has achieved efficient prevention of gasified ash water scale formation, met environmentally friendly emission requirements, provided stability and safety, with a scale dispersion rate of more than 95%, is non-toxic and pollution-free, and is suitable for high-concentration circulating water systems.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of dispersant preparation, and in particular to a phosphorus-free water dispersant and a preparation method thereof. Background Art
[0002] As the gasifier of coal-to-liquid gasification circulating water system runs for a long time, calcium and magnesium ions accumulate continuously in the system. In addition, the circulating water system has the characteristics of high temperature, high pressure and high turbidity, which causes frequent scaling of the equipment pipes of the synthesis gas washing system, quenching water treatment system and black water treatment system of the gasification device, short operation cycle of the gasifier and frequent inspection and maintenance. In order to solve the above problems existing in the device, the domestic coal gasification ash water system currently adopts the method of adding phosphorus-containing scale inhibitors and dispersants to control the scaling of the ash water system and ensure the normal operation of the coal gasification system. However, with the development of environmental protection, the state has made stricter regulations on the phosphorus content in industrial water pollutants. The existing phosphorus-containing system cannot meet environmental protection requirements. Therefore, the development of a phosphorus-free scale inhibitor and dispersant for coal gasification ash water circulation treatment is an urgent problem to be solved.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The first purpose of the present invention is to provide a phosphorus-free ash water dispersant, which has good effect, good stability, certain chlorine resistance and antioxidant properties, can effectively prevent the serious scaling problem of coal gasification ash water, and meet the environmental protection emission requirements for phosphorus, thereby ensuring the long-term stable operation of the coal gasification ash water system.
[0005] The second object of the present invention is to provide a method for preparing the above-mentioned phosphorus ash-free water dispersant, which has simple operation, mild operating conditions, no pollution, no discharge of three wastes, and is safe and environmentally friendly.
[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0007] The invention provides a phosphate-free water dispersant, which is mainly prepared from the following raw materials: by weight, 15-20 parts of maleic acid-acrylic acid copolymer, 10-15 parts of polyepoxysuccinic acid, 15-25 parts of acrylic acid-acrylate-sulfonate copolymer, 10-15 parts of hydrolyzed polymaleic anhydride, 8-12 parts of sodium lignin sulfonate, and an appropriate amount of water.
[0008] Preferably, as a further feasible scheme, based on weight percentage, maleic acid-acrylic acid copolymer is 16-18 parts, polyepoxysuccinic acid is 11-14 parts, acrylic acid-acrylate-sulfonate copolymer is 17-22 parts, hydrolyzed polymaleic anhydride is 11-14 parts, and sodium lignin sulfonate is 9-11 parts.
[0009] Preferably, as a further feasible scheme, based on weight percentage, 17 parts of maleic acid-acrylic acid copolymer, 13 parts of polyepoxysuccinic acid, 20 parts of acrylic acid-acrylate-sulfonate copolymer, 13 parts of hydrolyzed polymaleic anhydride, and 10 parts of sodium lignin sulfonate are used.
[0010] Preferably, the amount of water used is 40-50 parts by mass.
[0011] The phosphorus-free ash water dispersant of the present invention mainly comprises the following components that play a dispersing role: maleic acid-acrylic acid copolymer, hydrolyzed polymaleic anhydride, acrylic acid-acrylate-sulfonate copolymer. The three copolymers are compounded with each other. Since the molecular chain of the copolymer contains strong acid, weak acid and non-ionic groups at the same time, it can selectively adsorb on the surface of suspended matter, calcium carbonate crystals and inorganic suspended particles, so that the surface of the suspended matter carries a strong negative charge of the same nature. By utilizing the mechanism of like repels like, the crystallization induction period of scaling substances such as calcium carbonate is prolonged, the scaling of ash water is slowed down, and the effect of the crystallization center of suspended matter in ash water is reduced. The present invention has excellent dispersing performance. In particular, if a single copolymer is used, its uniform dispersion effect is not comprehensive enough and cannot achieve good results. The present invention not only improves the scale inhibition effect by compounding the three copolymers together for scale inhibition, but also gives a higher level of improvement in its antioxidant and anti-chlorination properties.
[0012] In addition, the addition of polyepoxysuccinic acid also achieves the effect of softening scale and reduces the probability of scale formation.
[0013] Of course, each component in the dispersant of the present invention needs to be controlled within an appropriate dosage range, especially for the main active ingredients, which may be added in a relatively large amount. However, the copolymer is relatively viscous, and if the dosage is too large, the state of the dispersant itself may change. Therefore, the dosage needs to be appropriately controlled.
[0014] In addition to providing a formula of a phosphorus-free water dispersant, the present invention also provides a method for preparing the phosphorus-free water dispersant, comprising the following steps:
[0015] Mix all the raw materials and stir for 130-220 minutes.
[0016] Preferably, the order of adding all the raw materials is water, acrylic acid-acrylate-sulfonic acid copolymer, polyepoxysuccinic acid, sodium lignin sulfonate, maleic acid-acrylic acid copolymer and hydrolyzed polymaleic anhydride.
[0017] Preferably, after adding water, acrylic acid-acrylate-sulfonic acid copolymer and polyepoxysuccinic acid, the temperature is controlled at 20-30° C., stirred for 30-60 minutes, and then other raw materials are added.
[0018] Preferably, among the other raw materials that continue to be added, after sodium lignin sulfonate is added, the temperature is controlled at 60-80° C., and after stirring for 45-60 minutes, the remaining raw materials are added.
[0019] Preferably, the stirring speed during the mixing process is between 50-70 rpm.
[0020] By limiting various operating parameters in the preparation method, the quality of the prepared fluorescent non-phosphorus scale inhibitor is improved.
[0021] In conclusion, the phosphorus-free ash water dispersant prepared by the above preparation method is green and environmentally friendly, and the synergistic effect between the components improves the dispersibility of the product, is phosphorus-free, non-toxic, and is beneficial to environmental protection. The scale inhibition and dispersion rate is above 95%.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The components of the ash water dispersant of the present invention have good synergy. It can selectively adsorb on the surface of suspended matter, calcium carbonate crystals and inorganic suspended particles, so that the surface of the suspended matter carries a strong negative charge of the same nature. By utilizing the mechanism of like charges repelling each other, the crystallization induction period of scaling substances such as calcium carbonate is prolonged, the scaling of ash water is slowed down, and the effect of the crystallization center of the suspended matter in the ash water is reduced.
[0024] (2) The phosphorus-free scale inhibitor and dispersant for coal gasification ash water described in the present invention contains hydroxyl, carboxylic acid, sulfonic acid, hydroxypropyl and other groups, and has the functions of chelation, dispersion, adsorption, lattice distortion, etc., so as to effectively prevent the formation of calcium carbonate, calcium sulfate, and barium sulfate crystals in water, and make the already formed crystals soft, thereby preventing the formation of hard scale.
[0025] (3) The pharmaceutical formulation of the present invention has good stability, certain chlorine resistance and antioxidant properties, and is suitable for use in a circulating water system with a high concentration ratio, which is beneficial to water conservation.
[0026] (4) The agent of the present invention does not contain phosphorus, is non-toxic, and is beneficial to environmental protection. The scale inhibition and dispersion rate is above 95%. DETAILED DESCRIPTION
[0027] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0028] Example 1
[0029] The specific preparation process of the phosphorus-free water dispersant is carried out according to the following steps:
[0030] 1. Prepare each raw material according to the following mass fractions:
[0031] 15 parts of maleic acid-acrylic acid copolymer, 15 parts of polyepoxysuccinic acid, 15 parts of acrylic acid-acrylate-sulfonate copolymer, 15 parts of hydrolyzed polymaleic anhydride, 8 parts of sodium lignin sulfonate and 40 parts of water;
[0032] 2. First, add purified water, acrylic acid-acrylate-sulfonic acid copolymer, and polyepoxysuccinic acid into the reaction kettle in sequence, control the temperature at 20°C, stir at 60 rpm, and stir for 60 min;
[0033] 3. Add sodium lignin sulfonate, control the temperature at 60°C, and stir for 60 minutes;
[0034] 4. Finally, add maleic acid-acrylic acid copolymer and hydrolyzed polymaleic anhydride into the stirring container in sequence. After stirring evenly for 60 minutes, the temperature will drop below 30°C to obtain the product.
[0035] Example 2
[0036] The specific preparation process of the phosphorus-free water dispersant is carried out according to the following steps:
[0037] 1. Prepare each raw material according to the following mass fractions:
[0038] 20 parts of maleic acid-acrylic acid copolymer, 10 parts of polyepoxysuccinic acid, 25 parts of acrylic acid-acrylate-sulfonate copolymer, 10 parts of hydrolyzed polymaleic anhydride, and 12 parts of sodium lignin sulfonate and 50 parts of water;
[0039] 2. First, add purified water, acrylic acid-acrylate-sulfonic acid copolymer, and polyepoxysuccinic acid into the reaction kettle in sequence, control the temperature at 30°C, stir at 50 rpm, and stir for 30 min;
[0040] 3. Add sodium lignin sulfonate, control the temperature at 80°C, and stir for 30 minutes;
[0041] 4. Finally, add maleic acid-acrylic acid copolymer and hydrolyzed polymaleic anhydride into the stirring container in sequence. After stirring evenly for 60 minutes, the temperature will drop below 30°C to obtain the product.
[0042] Example 3
[0043] The specific preparation process of the phosphorus-free water dispersant is carried out according to the following steps:
[0044] 1. Prepare each raw material according to the following mass fractions:
[0045] 16 parts of maleic acid-acrylic acid copolymer, 14 parts of polyepoxysuccinic acid, 17 parts of acrylic acid-acrylate-sulfonate copolymer, 14 parts of hydrolyzed polymaleic anhydride, 9 parts of sodium lignin sulfonate and 45 parts of water;
[0046] 2. First, add purified water, acrylic acid-acrylate-sulfonic acid copolymer, and polyepoxysuccinic acid into the reaction kettle in sequence, control the temperature at 25°C, stir at 70 rpm, and stir for 50 min;
[0047] 3. Add sodium lignin sulfonate, control the temperature at 70°C, and stir for 50 minutes;
[0048] 4. Finally, add maleic acid-acrylic acid copolymer and hydrolyzed polymaleic anhydride into the stirring container in sequence. After stirring evenly for 45 minutes, the temperature will drop below 30°C to obtain the product.
[0049] Example 4
[0050] The specific preparation process of the phosphorus-free water dispersant is carried out according to the following steps:
[0051] 1. Prepare each raw material according to the following mass fractions:
[0052] 18 parts of maleic acid-acrylic acid copolymer, 11 parts of polyepoxysuccinic acid, 22 parts of acrylic acid-acrylate-sulfonate copolymer, 11 parts of hydrolyzed polymaleic anhydride, and 11 parts of sodium lignin sulfonate and 45 parts of water;
[0053] 2. First, add purified water, acrylic acid-acrylate-sulfonic acid copolymer, and polyepoxysuccinic acid into the reaction kettle in sequence, control the temperature at 25°C, stir at 70 rpm, and stir for 50 min;
[0054] 3. Add sodium lignin sulfonate, control the temperature at 70°C, and stir for 50 minutes;
[0055] 4. Finally, add maleic acid-acrylic acid copolymer and hydrolyzed polymaleic anhydride into the stirring container in sequence. After stirring evenly for 45 minutes, the temperature will drop below 30°C to obtain the product.
[0056] Example 5
[0057] The specific preparation process of the phosphorus-free water dispersant is carried out according to the following steps:
[0058] 1. Prepare each raw material according to the following mass fractions:
[0059] 17 parts of maleic acid-acrylic acid copolymer, 13 parts of polyepoxysuccinic acid, 20 parts of acrylic acid-acrylate-sulfonate copolymer, 13 parts of hydrolyzed polymaleic anhydride, and 10 parts of sodium lignin sulfonate and 45 parts of water;
[0060] 2. First, add purified water, acrylic acid-acrylate-sulfonic acid copolymer, and polyepoxysuccinic acid into the reaction kettle in sequence, control the temperature at 25°C, stir at 70 rpm, and stir for 50 min;
[0061] 3. Add sodium lignin sulfonate, control the temperature at 70°C, and stir for 50 minutes;
[0062] 4. Finally, add maleic acid-acrylic acid copolymer and hydrolyzed polymaleic anhydride into the stirring container in sequence. After stirring evenly for 50 minutes, the temperature will drop below 30°C to obtain the product.
[0063] Comparative Example 1
[0064] The specific operation steps are the same as those in Example 5, except that the amount of acrylic acid-acrylate-sulfonate copolymer added is 10 parts.
[0065] Comparative Example 2
[0066] The specific operation steps are the same as those in Example 5, except that the amount of acrylic acid-acrylate-sulfonate copolymer added is 30 parts.
[0067] Comparative Example 3
[0068] The specific operation steps are the same as those in Example 5, except that the maleic acid-acrylic acid copolymer is not added.
[0069] Comparative Example 4
[0070] The specific operation steps are the same as those in Example 5, except that 5 parts of maleic acid-acrylic acid copolymer are used.
[0071] Experimental Example 1
[0072] The performance of the phosphorus ash-free water dispersants of Examples 1-5 and Comparative Examples 1-4 was evaluated: The water used in this experiment was circulating cooling water make-up water of a certain enterprise, and the water quality is shown in Table 1.
[0073] Table 1 Experimental water quality indicators
[0074]
[0075] The performance of the scale inhibitor was evaluated according to the national standard GB / T16632-2008 "Determination of performance of scale inhibitors for water treatment agents". The experimental water temperature was 80°C. The performance of this product was compared with that of commercially available products. The concentration of the test agent was tested using an ultraviolet spectrophotometer with an absorption wavelength of 375nm. The concentration of the agent was calculated by measuring the absorbance. The results are shown in Table 2.
[0076] Table 2 Performance evaluation results
[0077]
[0078] It can be seen from Table 2 above that the scale inhibition and dispersion rate of the phosphorus-free ash water dispersant of the present invention is above 95%, which is significantly better than a certain commercially available ash water dispersant, and the raw materials used do not contain phosphorus, thus preventing the pollution of water bodies by phosphorus.
[0079] In addition, it can be known from the performance evaluation results of Comparative Examples 1-4 of the present invention that the three main agents important to the present invention all need to be controlled within an appropriate range. If the amount added is too large or too small, the experimental effect will be affected. Moreover, since the three have a synergistic effect, it can be seen from the results of Comparative Example 3 that when the maleic acid-acrylic acid copolymer is not added, its scale inhibition effect is significantly reduced, but when a small amount is added, the overall scale inhibition effect may not be seriously reduced. This shows that when a small amount is added, due to the formation of a composite relationship, it will still have a good scale inhibition effect, but when it is not added at all, this balance relationship is directly destroyed, so its scale inhibition effect will drop sharply. In short, all components of the dispersant of the present invention must be included, and none of them can be missing. If any one is added less or the component is not set within an appropriate dosage range, it will have a certain impact on the final scale inhibition effect.
[0080] Although the present invention has been illustrated and described with specific embodiments, it will be appreciated that many other changes and modifications may be made without departing from the spirit and scope of the present invention. Therefore, it is intended to include all such changes and modifications within the scope of the present invention in the appended claims.
Claims
1. A phosphorus-free water dispersant, characterized in that: It is mainly prepared from the following raw materials: by weight, 17 parts of maleic acid-acrylic acid copolymer, 13 parts of polyepoxysuccinic acid, 20 parts of acrylic acid-acrylate-sulfonate copolymer, 13 parts of hydrolyzed polymaleic anhydride, 10 parts of sodium lignin sulfonate, and an appropriate amount of water; The steps of preparing the phosphorus-free water dispersant are: The addition order of all raw materials is water, acrylic acid-acrylate-sulfonic acid copolymer, polyepoxysuccinic acid, sodium lignin sulfonate, maleic acid-acrylic acid copolymer and hydrolyzed polymaleic anhydride.
2. The phosphorus-free water dispersant according to claim 1, characterized in that: The amount of water used is 40-50 parts by mass.
3. The method for preparing the phosphorus-free water dispersant according to any one of claims 1 to 2, characterized in that: The steps include: Mix all the raw materials and stir for 130-220 minutes.
4. The preparation method according to claim 3, characterized in that: After adding water, acrylic acid-acrylate-sulfonic acid copolymer and polyepoxysuccinic acid, the temperature is controlled at 20-30°C, and after stirring for 30-60 minutes, other raw materials are added.
5. The preparation method according to claim 4, characterized in that: Among the other raw materials that continue to be added, add sodium lignin sulfonate and control the temperature to 60-80°C. After stirring for 45-60 minutes, add the remaining raw materials.
6. The preparation method according to claim 5, characterized in that: The stirring speed is 50-70 rpm.
Citation Information
Patent Citations
Environment-friendly efficient scale inhibitor of bittern
CN103964590A
Scale inhibition dispersant and preparation method thereof
CN111170478A
Fluorescent phosphorus-free scale inhibitor and preparation method thereof
CN112079450A
